A case of refractory tumor bleeding from an ampullary adenocarcinoma: Compression hemostasis with a self‐expandable metallic stent. Issue 1 (22nd August 2021) - Daiku, Kazuma; Ikezawa, Kenji; Maeda, Shingo; Abe, Yutaro; Kai, Yugo; Takada, Ryoji; Yamai, Takuo; Fukutake, Nobuyasu; Nakabori, Tasuku; Uehara, Hiroyuki; Ohkawa, Kazuyoshi
Abstract: Although patients with ampullary cancers frequently experience obstructive jaundice and tumor bleeding, there have been few reports on efficient management of refractory hemorrhage after conservative treatment. In this report, we describe a case of refractory bleeding from a 15‐mm ampullary adenocarcinoma. A Japanese woman in her 60s was urgently hospitalized for cholangitis, pancreatitis, and sepsis treatment. Investigation with a side‐viewing duodenoscope revealed an ulcerated ampullary adenocarcinoma. After the patient underwent anticoagulation therapy for pulmonary thromboembolism, the tumor bleeding gradually increased, resulting in severe anemia. Because the anemia did not improve with fasting or discontinuation of the anticoagulation therapy, the patient underwent repeated red blood cell transfusions. As no hemobilia was observed in the bile juice aspirated during endoscopic retrograde cholangiography, we supposed that the bleeding originated from the ulcerative cancer surface. We did not perform thermal therapy because we considered that it would worsen the bleeding. Abdominal angiography showed no pseudoaneurysms or extravasation. Ultimately, we performed transpapillary placement of a fully covered self‐expandable metallic stent (SEMS) with an anchoring double pigtail plastic stent that resulted in successful hemostasis. In this case, the mechanism of hemostasis was not presumably explained by direct compression of the bleeding point but by indirect compression. When tumor volume is small, the radial force of the SEMS may cause compression of the tumor volume, leading to shrinkage of the bleeding blood vessels. In conclusion, covered SEMS placement could be an efficient treatment for refractory ampullary cancer bleeding, even from an ulcerated cancer surface.